PELAPISAN UREA DENGAN ARANG AKTIF YANG DIPERKAYA MIKROBA DAPAT MEMPERCEPAT PENURUNAN KONSENTRASI RESIDU INSEKTISIDA HEPTAKLOR DI LAHAN SAWAH - Wahyuni, Sri; Indratin, nFN; Sulaeman, E; Ardiwinata, A. N. (Sekretariat Badan Penelitian dan Pengembangan Pertanian, 2016)
Heptachlor insecticide is a toxic organochlorine insecticide, persistent and bio-cummulative in the environment. Remediation using actived carbon and microbial is a solution to pollution due to pesticide in the environment.The objective of this study was to obtain fertilizer technology using urea with activated carbon and enriched with microbes degrading heptachlor insecticide in order to reduce the insecticide residue in paddy fields. The research was conducted at the Jakenan Experimental Station between February to September 2012. The soil used as the planting medium was brought from the village Sukamenak, District Rawagempol Wetan, Karawang. The experiment was conducted in the field at micro-plot scale with lysimeter, and using a randomized block design (RBD) with 3 replications and 6 fertilizer treatments ( control , prill urea , urea with activated carbon maize cobs ( UAATJ ) , urea with activated carbon coconut shell ( UAATK ) , urea with activated carbon cob corn + microbes ( UAATJM ) , urea with activated carbon coconut shell + microbes ( UAATKM ). The plants used were from Inpari 13 variety. The insecticide residue analysis was performed in the Residu Bahan Agrikimia (RBA) laboratory of Balingtan. The results showed significant orthogonal countrast tests of different treatments. The highest reduction of residual insecticide was observed in urea coated with activated carbon cob corn and enriched with microbial consortia degrading POPs, which was 36.30 %. It is suspected that activated carbon coated cob corn with microbial enrichment was favored as its home and the microbes utilized carbon sources of heptachlor as the food.